Time, space, and material : the mechanics of layering in architecture - Schultz, Anne-Catrin (Stuttgart : Edition Axel Menges, 2015)
This book examines the application of the principle of layering in architecture, its mechanics, possible application and meaning. Layering is widely used in the discussions of the 20th and 21st centuries architecture but rarely defined or examined. Layering bridges the tectonics of structure and skin, offers a system for the creation of different architectural spaces over time and functions as a design principle without hierarchy. Three types of layering are identified: a chronological sedimentation of planes materializing changes over time (temporal layering), the additive sequence of spaces (spatial layering), and the stratification of individual planes (material layering).
Introduction -- The meaning of layering -- Layering in architecture -- A history of layered architecture -- Temporal layering : building in historic context -- Spatial layering : in-depth sequences of hierarchy and program -- Material layering : multiple-skin envelopes -- Conclusion.
Includes bibliographical references and index.
Keywords: Architectural design